Peranan Guru Bimbingan dan Konseling dalam Mengatasi Kesulitan Membaca pada Remaja Melalui Klinik Baca di SMPN 1 Kedawung - Munah, Anis Satul; Ristianty, Asti Dwi; Indah, Suci Tiara; Karminatuzzahra, Mimi; Putri, Vany Dwi (PT Hakhara Akademia Indonesia, 2024)
This research aims to raise a case in a school in the field of learning that has been handled by a guidance and counseling teacher. In this study, researchers found one of the problems in the field of learning, namely difficulty reading. This research was conducted at SMPN 1 Kedawung, Cirebon Regency. The data collection technique used in this research was an interview with Mrs. Sri as the guidance and counseling teacher coordinator. The difficulty experienced by one of the students at SMPN 1 Kedawung was a class IX male student. Seeing that their students were having difficulty reading, the guidance and counseling teacher there collaborated with the Indonesian language teacher to implement a reading clinic program. The reading clinic itself is a program in the form of additional classes for students who have difficulty reading. The results of the reading clinic show quite good progress. This is evidenced by the reduction in reports from teachers of other subjects.